دراسة بعض الخصائص الكيميائية لمياه الأمطار في مواقع مختلفة من محافظة اللاذقية - حسين ميس محمد; كبيبو عيسى نور الدين; هيفا سوسن عبدالله (Latakia University Journal -Biological Sciences Series, 2013)
نفذت هذه الدراسة في مواقع مختلفة من ريف محافظة اللاذقية ( قريتي الحمراء والصباحية التابعتين لناحية ربيعة، وقرية عين الزرقا التابعة لبلدة مشقيتا)، وتم تسجيل 14 هطول مطري precipitation تسبب في حدوث جريان سطحي وانجراف مائي خلال فترة الدراسة (الموسم المطري 2011/2012). جمعت عينات من مياه الأمطار لكل هطول مطري بواسطة مقاييس مطرية وضعت في مواقع التجربة، ثم نقلت العينات إلى المخبر. تم قياس درجة pH هذه العينات ثم تحليلها باستخدام جهاز الكروماتوغرافيا الشاردية Ion chromatography (IC تقنية التنقية والعزل ). تشير النتائج إلى: الطبيعة القلوية لماء الهطول المطري في المنطقة الريفية المدروسة (درجة الـ pH تتراوح بين 7.1 و 7.8)، وتأثير الرياح التي تهب في فصل الربيع وما تحمله معها من غبار التربة على بعض الخصائص الكيميائية للهطول المطري. كما يبين تحليل البيانات إحصائياً تفوق الهطول المطري في فصل الربيع على باقي هطولات الموسم بتركيز شوارد الكبريتات والكلور والصوديوم والأمونيوم ( ppm 15.9 ، 10.8 ، 3.7 ، 3 ) ولم تظهر فروق معنوية بتركيز شاردتي الكالسيوم والمغنزيوم في ماء الهطولات المطرية المسجلة . The research has been conducted in different sites in lattakia, Alhamra and alsabahia villages of Rabea and Aen alzarqa of Mashqeta. 14 cases of precipitation was marked which caused runoff and water erosion of soil during the research (seasonal rainfall in 2011/2012). Samples of rain water of every precipitation case were collected. by using rain gauges that were installed in the research sites. After that, samples were moved to the laboratory. The pH was determined after that the samples were analyzed by using an ion chromatography device(IC). The results indicate the alkaline nature of precipitation in the target rural area (pH 7.1-7.8), and the effect of spring wind and the soil dust that it carries along on some chemical characteristics of precipitation. Furthermore, data statistical analysis indicates that the concentration of sulfates, chloride, sodium, ammonium during spring is more than that other marked during the precipitation cases and no significant differences in the concentration of Calcium and Magnesium ions of the target precipitation.